MAPPING THE POTENTIAL OF MARINE LIVING RESOURCES IN OUTER ISLAND OF SOUTHWEST MOLUCCAS - Thomas Mahulette; Andarias Steward Samusamu (Research Center for Fisheries, 2020)
Southwest Moluccas or Maluku Barat Daya (MBD) District is one of the small islands located in the southeastern part of outer ring of Indonesian Archipelagic States. There are 17 sub districts covering 48 islands lie scattered in the region in which 31 islands among them were not inhabited. The island has a total population of about 72.300, while 4.069 (5.6 %) are fisherman. The annual fish production in 2017 was reported at 8,971 tons consists of: small pelagic fish (48%), demersal (37%), and large pelagic (15%). The coastal ecosystems include of coral reefs (595 Ha), mangrove (7.8 Ha), and sea grass (57 Ha). Seaweed harvesting and cultivation are ones that would be developed as an alternate livelihood for the community. The goal of this research was to describe a general situation of community livelihood that supported by the role of marine fisheries. The general description of fishing boat and fishing gear, annual production, distribution of fisherman and household around the islands were discussed. The fisheries category were small scale within about one day fishing. The environmental parameters such as monthly air temperature, rainfall and wind speed were plotted as supporting information. The population distribution and fisherman were also used as a base line parameter to elaborate the potential of marine living resource in the interested area. Those resources were described with existing small scale fisheries issues based on limited serial data that gathered through field observation. The secondary data such as Mollucas Southwest District (MBD) annual data from the Local Statistical Board (BPS) annual report were also used in this paper.